Inconsistencies of a purported probability current in the Duffin-Kemmer-Petiau theory - Cardoso, T. R. [UNESP]; Castro, L. B. [UNESP]; de Castro, A. S. [UNESP] (Elsevier B.V., 2008)
The Duffin-Kemmer-Petiau (DKP) equation with a square step potential is used in a simple way with polymorphic purposes. it proves adequate to refuse a proposed new current that is currently interpreted as a probability current,to show that the Klein paradox does exist in the DKP theory and to revise other minor misconceptions diffused in the literature, (C) 2008 Elsevier B.V. All rights reserved.